Generation of social anomie at the sight of «organized skepticism» - Grishchenko, Zhanna M.; Scholkova, Tatiana V. (Journal of the Belarusian State University. Sociology, 2019)
The article is a logical continuation of the theme of the characterological features of the post-Soviet generation of students, whose socialization took place in the conditions of total anomie in society. In the center of research interest this time-the problem of self-realization of modern students, presented as a search for ways and means of implementation of the program of personal success in life. The empirical basis of the trends objectified in the article includes the results of quantitative and qualitative research methods with a focus on the meanings programming the actual patterns of behavior of generation Z. in Parallel, the discussion on the methodological features of modern sociology, the reactivity of its tools and the approbation of techniques to increase its sensitivity to the measurement of meanings.